Quantitative Measurement and Analysis of the Radial Peripapillary and Central Macular Microvasculature Density in Early Open-Angle Glaucoma Using OCT Angiography - Abdala, Majdi Abdulhamid; Masoud, Suliman Mohamed; Geilani, Nadia Abdelsalam (Libyan International Medical University Journal, 2024)
Background Glaucoma is a prevalent cause of visual impairment, and early detection is critical to prevent progressive vision loss. Optical coherence tomography angiography (OCT-A) enables visualization of retinal and optic nerve microvasculature and holds promise for early glaucoma detection.Aims This study aims to assess microvasculature density alterations in glaucoma using OCT-A.Methods An observational cross-sectional case–control study was conducted at Benghazi Eye Hospital in Libya from December 2022 to August 2023. It included 160 eyes of 126 patients diagnosed with primary open-angle glaucoma and 120 eyes of 96 control subjects. OCT-A was performed using the Swept-Source OCT DRI Triton. Vessel density measurements were obtained from OCT-A images using new built-in software within the device. The data presented as mean ± standard deviation and percentages were analyzed using SPSS. The statistical significance of the differences between different groups was determined using independent t-tests, and the level of significance was set at p-value less than 0.05.Results OCT-A demonstrated significantly reduced microvasculature density in glaucoma eyes across all optic nerve sectors including the inferior (29.0%), superior (25.2%), central (23.5%), nasal (9.9%), and temporal sectors (9.3%; p < 0.02). Moreover, glaucoma patients exhibited a significant reduction in vessel density in the superior macula (17% reduction), the temporal (15.7%,), nasal (12.9%), and inferior sectors (12.6%) (p < 0.002). No statistical difference was seen with vessel density of the central sector (0.49%, p >0.05).Conclusion OCT-A demonstrated significant reductions in microvasculature density in glaucoma patients compared with healthy controls. These findings support the association between glaucoma and vascular changes. Additionally, the TOPCON Swept-Source OCT DRI Triton new software shows promise as a valuable tool for early detection and monitoring of glaucoma-related vascular changes.
Keywords: early detection; glaucoma; microvasculature density; optical coherence tomography angiography; TOPCON Swept-Source OCT DRI Triton